Impaired Fibrinolytic Capacity and Tissue Plasminogen Activator Release in Patients with Restenosis after Percutaneous Transluminal Coronary Angioplasty (PTCA) - Kirschstein, W; Simianer, S; Dempfle, C E; Keller, H; Stegaru, B; Rentrop, P; Heene, D L (Thrombosis and Haemostasis, 1989)
To assess the role of the fibrinolytic system in the pathogenesis of restenosis after percutaneous transluminal coronary angioplasty (PTCA), we determined the components of this system in a retrospective study, including 16 patients with restenosis (gr. A) and 19 patients with long-term success (gr. B). In both groups at baseline fibrinolytic activity (FA) is unchanged, whereas tissue plasminogen activator antigen (tPA-Ag) is significantly increased (gr. A: 147.0%; gr. B: 139.8%; p <0.01). Fibrinolytic capacity (FC) and tPA-Ag release are significantly reduced in the restenosis group (FC: 46.5%, p <0.05; tPA-Ag release: 48.3%, p <0.01) compared to normal controls as well as to gr. B (FC: 84.3%, p <0.05; tPA-Ag release: 79.0%, p <0.05).Relating to the contact activation system, F XII (79.5%, p <0.05) is significantly, and F XI (82.3%) is clearly reduced in gr. A. Protein C (PC) is significantly elevated in gr. B (117.5%, p <0.05). There is a negative correlation between plasminogen activator inhibitor (PAI 1) and HDL-cholesterol (r = 0.37, p <0.05).It appears, that there is a typical pattern of defective fibrinolysis in patients with restenosis after PTCA and that this might be a pathogenetic factor in the development of restenosis.
Keywords: PTCA; Restenosis; Plasminogen activator inhibitor; Tissue plasminogen activator; Protein C